2021
DOI: 10.1021/acs.jpclett.1c02027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and New Insight for the Drag Reduction of Turbulent Flow with Polymers and Its Degradation Mechanism

Abstract: A physicochemical understanding of the mechanism of turbulent flow drag reduction with polymer and its degradation is of great interest from both science and industry perspectives. Although the correlation based on the Fourier series has been proposed to predict the drag reduction and its degradation, its physical meaning was not clear until now. This letter aims to clarify this issue. We develop a comprehensive model to predict the drag reduction and degradation of polymers in turbulent flow from a chemical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Hoyt et al , proposed one model for the prediction of friction factor: R e f / d was a constant when polymer type, molecular weight, and polymer concentration were the same. In our previous work, , we extract data from previous research and rearrange them in a Prandtl–von Karman coordinate with log 10 ( Re f ) vs 1 / f . The results showed that all data can be fitted in a straight line, which follows the format in eq .…”
Section: Resultsmentioning
confidence: 99%
“…Hoyt et al , proposed one model for the prediction of friction factor: R e f / d was a constant when polymer type, molecular weight, and polymer concentration were the same. In our previous work, , we extract data from previous research and rearrange them in a Prandtl–von Karman coordinate with log 10 ( Re f ) vs 1 / f . The results showed that all data can be fitted in a straight line, which follows the format in eq .…”
Section: Resultsmentioning
confidence: 99%
“…However, among these agents, DRPs have been considered the most efficient (Eshrati, Al-Wahaibi et al 2022). Additionally, a literature survey of the published work on DRPs in multi-phase flow pipelines assured the growing interest , Edomwonyi-Otu, Dosumu et al 2021, Zhang, Dai et al 2021, Eshrati, Al-Wahaibi et al 2022, Mortimer and Fairweather 2022, Tan, Hu et al 2022. In addition to drag reduction, the aforementioned studies reported that DRPs can change the configurations of the co-existing phases.…”
Section: Introductionmentioning
confidence: 99%